The Concept of “Spiritual Cinema” in the Philosophy of Gilles Deleuze - Baranova, Jūratė (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English] Is it possible to include cinema in the process of education of the spiritual values? This rhetorical question can be answered negatively. It is possible that the cinema cannot solve such kind of a task. It is probable that even when cinema is used in seeking to establish certain spiritual values, it is not able and possesses no means to reach the primary goal. This article begins with a provocative question: why it is possible to doubt the possibility of sacral cinema? Lithuanian philosopher Tomas Sodeika offered to treat religious art as an oxymoron, arguing that it is incapable to reproduce sacrum in the visual image. This article suggests an alternative strategy for approaching this problem: it deals with the concept of spiritual cinema reflected by Gilles Deleuze in his philosophy of cinema. The author of this article comes to that conclusion that Deleuze prolongs the Kierkegaardian concept of the three dimensions of spirit by adding the forth (time) and the fifth (spirit) dimensions, and with this finds it possible to suggest a type of spiritual cinema parallel to religious (which is close to revolutionary) cinema. It allows us to avoid the radical opposition between matter and spirit. In this article, the cinematography of Bresson is treated as an example of spiritual cinema, reflected by Deleuze and by Tarkovsky. The basic precondition of the founding of spiritual cinema is, according to the author, a necessary possibility that Deleuze distinguished in a specific film – not fully invisible, but possibly fluctuating beyond the field of vision (hors-champ).